2018
DOI: 10.5935/abc.20180091
|View full text |Cite
|
Sign up to set email alerts
|

Early Assessment of Right Ventricular Function in Systemic Lupus Erythematosus Patients using Strain and Strain Rate Imaging

Abstract: BackgroundRight ventricular function is a crucial factor of the prognosis of systemic lupus erythematosus (SLE).ObjectivesTo evaluate the right ventricular function in SLE patients with different degrees of pulmonary hypertension (PH) by strain and strain rate imaging.MethodsA total of 102 SLE patients and 30 healthy volunteers were studied between October 2015 and May 2016. Patients were divided into three groups according to pulmonary artery systolic pressure (PASP) estimated by echocardiography: group contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…Leal et al reported a significant deterioration in RVLS among adolescents with SLE [60]. Similar findings were reported in adults with SLE [61]. However, they reported significantly reduced RVLS in basal, middle, and apical segments only in patients with increased pulmonary pressure (>30 mmHg), but not in those with normal pulmonary pressure [61].…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 56%
“…Leal et al reported a significant deterioration in RVLS among adolescents with SLE [60]. Similar findings were reported in adults with SLE [61]. However, they reported significantly reduced RVLS in basal, middle, and apical segments only in patients with increased pulmonary pressure (>30 mmHg), but not in those with normal pulmonary pressure [61].…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 56%
“…Los estudios reportan entre 40 -50% de afección cardíaca en las autopsias de pacientes lúpicos, pero solo se reporta entre el 7 -10% de casos en vida (15,16) . El análisis de la deformación miocárdica a través del método de speckle tracking es una técnica semiautomática de uso creciente en los últimos años que ha mostrado ser útil en diferentes escenarios clínicos como la enfermedad reumatológica, sobre todo en la afección cardíaca subclínica (17)(18)(19) .…”
Section: Discussionunclassified
“…Another study has reported that the survival rates of patients with SLE who develop PH seem lower than those of individuals with primary PH. 6 The findings of the study by Luo et al 5 allow us to speculate that RV dysfunction is the mediator of the high mortality risk in that group of individuals. Those findings suggest that the use of strain to analyze RV systolic function in SLE can select patients in a subclinical phase who require careful surveillance and early therapy to prevent the development of RV failure and cardiovascular complications.…”
mentioning
confidence: 95%
“…The study by Luo et al, 5 published in this issue of the Arquivos Brasileiros de Cardiologia , shows that the assessment of strain and strain rate by use of 2D-STE can detect early RV dysfunction in individuals with systemic lupus erythematosus (SLE) associated with mild and subclinical pulmonary hypertension [PH: systolic pulmonary artery pressure (SPAP) between 30 and 50 mmHg]. It is worth noting that, considering the other conventional and nonconventional parameters of RV size and systolic function, RV dysfunction was only diagnosed in individuals with moderate to severe PH (SPAP ≥ 50 mmHg).…”
mentioning
confidence: 98%